Chloroplast capture and range extension after hybridization in taro (Colocasia esculenta) - Matthews, P. J.; Hossain, M.A; Sookchaloem, D.; Nguyen, Van Du; Wong, Sin Yeng; Joling, Jyloerica; M.E, Schranz6; F. T., Bakker6; E., Tabuchi; I., Ahmed; A., Hay (John Wiley & Sons Ltd., 2024)
Complete chloroplast genomes of 17 samples from six species of Colocasia (Araceae) were sequenced, assembled, and aligned together with two previously reported complete genome sequences from taro (Colocasia esculenta). Analysis provides a well-supported phylogenetic tree for taro and closely-related wild Colocasia species in Southeast Asia. Two chloroplast lineages (CI and CII) form a well-defined haplotype group and are found in cultivated taros known as var. esculenta (dasheen, CI), var. antiquorum (eddoe, CII), and in a widespread, commensal wild form known as var. aquatilis (CI). A third lineage (CIII) is also found in wild taros known as var. aquatilis and in the wild species C. lihengiae, C. formosana, and C. spongifolia. We suggest three different scenarios to explain the grouping of CIII wild taros (C. esculenta) with other wild Colocasia species. Chloroplast lineages CI and CIII in C. esculenta and an unknown parent species may be involved in an as yet undated history of hybridization, chloroplast capture, and range extension. Substantial taxonomic revision may be needed for C. esculenta after further studies of morphological and genetic diversity within the crop, in wild populations, and in closely related wild species. The results also point to the Bengal delta as a region of key interest for future research on the origins of tropical wetland taros.